PENGELOLAAN E-RAPORT DI SEKOLAH MENENGAH KEJURUAN (SMK) SE-KECAMATAN KURANJI KOTA PADANG - Sri Wahyuni; Hade Afriansyah; Jasrial Jasrial; Widiawati Widiawati (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to describe the management of e-Report Cards in Vocational High Schools (SMK) throughout Kuranji District, Padang City, reviewed from the aspects of planning, organizing, implementing, and supervising. Method: This study uses a quantitative approach with descriptive methods. The study population is all 226 SMK teachers in Kuranji District, Padang City. The research sample is 58 people who were determined using the proportionate stratified random sampling technique. Data were collected through a Likert scale questionnaire that has met the validity and reliability tests. Data were analyzed using descriptive statistics through the calculation of the average value and Respondent Achievement Level (TCR). Results: The results of the study indicate that the management of e-Report Cards in Vocational High Schools (SMK) throughout Kuranji District, Padang City is in the good category with an average value of 4.40 and a TCR of 88.00%. The implementation indicator received the highest score with an average of 4.45 and a TCR of 89.02%. The monitoring indicator received the lowest score with an average of 4.28 and a TCR of 85.60%. Novelty: This study provides an empirical overview of e-Report Card management in vocational high schools based on the POAC management function, which includes planning, organizing, implementing, and supervising aspects.